2009
DOI: 10.17221/38/2008-pps
|View full text |Cite
|
Sign up to set email alerts
|

Apple burrknots involved in trunk canker initiation and dying of young trees

Abstract: Conditions associated with an unusually high occurrence of burrknots in two young commercial apple orchards at two locations, Těšetice and Stošíkovice, South Moravia, the Czech Republic, were analysed. In the first orchard, planted in spring 2003, the occurrence of burrknot on trees of cvs. Early Smith, Jonagold and Gala on M.9 rootstock was evaluated. In the second orchard, planted in autumn 2002, cv. Gala on M.9 rootstock was assessed. Planting material used at each location was obtained from the same commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Delicious Anbari, however scions of the other four apple cultivars (Royal Gala, Double Red, Golden Delicious, and Granny Smith) did not show any disease symptoms. Similarly, the stem associated apple tree viruses such as Apple stem pitting virus (ASPV) and Apple stem grooving virus (ASGV) were detected frequently in the rootstock and scion parts SFW -shoot fresh weight; RFW -root fresh weight; SDW -shoot dry weight; RDW -root dry weight; DS -disease severity (%) *correlation is significant at the 0.05 probability level; **correlation is significant at the 0.01 probability level of Jonagold and Early Smith cultivars and to the lower extent in Gala cultivar (Kůdela et al 2009). Therefore, cv.…”
Section: Discussionmentioning
confidence: 99%
“…Delicious Anbari, however scions of the other four apple cultivars (Royal Gala, Double Red, Golden Delicious, and Granny Smith) did not show any disease symptoms. Similarly, the stem associated apple tree viruses such as Apple stem pitting virus (ASPV) and Apple stem grooving virus (ASGV) were detected frequently in the rootstock and scion parts SFW -shoot fresh weight; RFW -root fresh weight; SDW -shoot dry weight; RDW -root dry weight; DS -disease severity (%) *correlation is significant at the 0.05 probability level; **correlation is significant at the 0.01 probability level of Jonagold and Early Smith cultivars and to the lower extent in Gala cultivar (Kůdela et al 2009). Therefore, cv.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of burrknots is peculiar to the genetic constitution of the cultivar, not being due to infection by biological agents (KUDELA et al, 2009). Rootstocks differ in the sensitivity degree to this disorder, being very marked in MM-111, MM-106, M-7 and M-26.…”
Section: Rootstocks For Apple Tree Cropmentioning
confidence: 96%
“…In the present study, 1.46 and 1.26 burrknots were present along the tree trunks of M.9 and of the combination Marubakaido/M.9, respectively, which are significantly higher averages than those of the Geneva rootstocks. Studies conducted in the Czech Republic suggested that burrknots on apple tree trunks can restrict the development of the plant, affecting fruit production, and may also facilitate the introduction of canker diseases, which could cause premature tree death (Küdela et al, 2009).…”
Section: Genotypementioning
confidence: 99%